Gender Differences in Vault Landing Location During the Artistic Gymnastics Competition of the 2000 Olympic Games: Implications for Improved Gymnast/Mat Interaction - McNitt-Gray, J.; Costa, K.; Mathiyakom, W.; Requejo, P. (coachesinfo.com)
As expected, the feet of the male gymnasts tended to land further from the vaulting horse than the feet of the female gymnasts. The separation between landing mats, however, was located in a region where many male gymnast landed. The difference in mat deformation characteristics near mat creases and/or mat separations may induce an unexpected change in loading conditions, particularly if the crease and/or separation are visually obscured from the gymnast. Unexpected changes in mat deformation may produce unexpected loading characteristics that may prove to be detrimental to the gymnast. Therefore, we suggest that the location of mat creases and/or mat separations be located in regions other than those used by the gymnast when dismounting and/or unexpectedly falling from the apparatus. Manufacturers designing vaulting landing surfaces need to consider these gender differences in landing location when deciding where to place mat creases and/or separations between adjacent mats.